Design and Study of Fractal Optical Modulator for Infrared Transmitted Signal - A. A. Shehab, A. A.; A. A. Mohammad, A. A.; A. R. Salihand, A. R. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The optical modulator was designed by using iterated function systems (IFSs) by IFS Construction Kit program. The modulator was inserted into the optical system using ZEMAX optical design program. In this program, it is assumed that the modulator is made from one of Ø¢ the infrared transmitting materials. Eight materials at room temperature were used in this study; these are IRTRAN materials, Si, and Ge for the range of 3-9 l-lm. Systems were evaluated and analyzed by using different criteria, including spot diagram, modulation transfer function, and point spread function. The effect of optical modulator change with the chang of Ø¢ its material results in focusing of functions and frequencies as required. Root mean square and geometrical spot sizes decrease with the increase of the refractive index, while the maximum spatial frequency increases.